Chapter Designing Heterogeneous-mHealth Apps for Cystic Fibrosis Adults - Vagg, Tamara (InTechOpen, 2020)
In this chapter, we will discuss the design and development of a patient passport mHealth application for Cystic Fibrosis adults from ideation to app-store release. By allowing the patients access to their own unique data, it is anticipated that it will be of benefit when travelling abroad and between CF centres. The design process followed a pipeline we developed that is informed by patient and healthcare professional input. The app structure resembles an Irish patient file and is divided into three categories: "My CF Info", "My Medical History", and "My Clinical Appointments". My CF Info allows the patient to store personal information such genotype, medical team contact information, physiotherapy, allergies, and medications. My Medical History allows the user to record information such as CF renal disease, CF diabetes, and the insertion/removal of a portacath/gastrostomy tube. My Clinical Appointments allows the user to record the type of appointment (annual assessment, clinic, other) and all information that would ordinarily be inserted into a patient file such as weight, height, spirometry and other comments. Weight and lung function are also displayed in a plot graph. The app has undergone pilot testing with five CF adults before being rolled out onto the Google Play Store.